THE EFFECT OF A COMBINATION OF SEED COATING BASED ON Trichoderma sp. AND TYPES OF COATING MATERIALS ON THE VIABILITY AND VIGOR OF CORN (Zea mays L.) SEEDS DURING STORAGE - Adinda Putri Virgia; Siti Latifatus Siriyah; Elia Azizah (Universitas Veteran Bangun Nusantara, 2026)
The decrease in seed viability and vigor during storage is one of the obstacles in maintaining the physiological quality of corn seeds. This study aims to determine the effect of Trichoderma sp.-based seed coating with several types of coating materials on the viability and vigor of corn seeds (Zea mays L.) during 3 months of storage, and to obtain the best treatment in maintaining the physiological quality of seeds. The study was conducted at the Agronomy Laboratory, Faculty of Agriculture, Singaperbangsa University, Karawang, from January to May 2026 using a single factor Completely Randomized Design (CRD) with 9 treatments and 4 replications. The data were analyzed using variance analysis and further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the study showed that Trichoderma sp.-based seed coating with several types of coating materials had a significant effect on the viability and vigor of corn seeds during storage. The negative control and sodium alginate treatments were the best coating materials for maintaining seed viability and vigor during 3 months of storage. Keywords: Germination, seed deterioration, seed storage, sodium alginate